Adoption to online collaboration in the Yemeni construction industry [electronic resource] - Mohammed Abdullah Musaed Al-Fareh, 1985- (2012)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2012